Heterometrus spinifer: An Untapped Source of Anti-Tumor Molecules - Soopramanien, Morhanavallee (2020)
Despite intensive research, cancer incidence and mortality continue to rise. Consequently, the necessity to develop effective anti-cancer therapy is apparent. We have recently shown that the gut bacteria of animals living in polluted environments, such as crocodiles, are a potential source of novel anti-tumor molecules. To extend this work to other resilient species, we investigated the anti-tumor effects of gut bacteria of Heterometrus spinifer (a scorpion). Bacteria from the feces and gut were isolated, identified and evaluated for their anti-tumor effects. Bacterial-conditioned media was prepared in Roswell Park Memorial Institute (RPMI) 1640 media, and cytotoxicity and growth inhibitory properties were examined against cervical (HeLa) cancer cells. Liquid chromatography–mass spectrometry (LC-MS) was conducted to establish the identity of the molecules. Eighteen bacteria species from the gut (HSG01-18) and ten bacteria species from feces (HSF01-10) were tested for anti-tumor effects. Bacterial-conditioned media from scorpion gut and feces exhibited significant growth inhibitory effects against HeLa cells of 66.9% and 83.8%, respectively. Microscopic analysis of cancer cells treated with conditioned media HSG12 and HSG16 revealed apoptosis-like effects. HSG12 was identified as Pseudomonas aeruginosa and HSG16 was identified as Bacillus subtilis. Both conditioned media exhibited 100% growth inhibitory effects versus a selection of cancer cells, comprising cervical, breast and prostate cancer cells. LC–MS indicated the presence of 72 and 38 compounds, detected from HSG12 and HSG16, respectively. Out of these compounds, 47 were successfully identified while the remainder were unidentified and are possibly novel. This study suggests that the fecal and gut microbiota of scorpions might possess molecules with anti-cancer properties, however, further intensive research is needed to assess these expectations.